Ultraviolet spectroscopy of AlO from first principle. (July 2023) - Bai, Tianrui; Qin, Zhi; Liu, Linhua
Highlights: Ab initio PECs, TDMs and partition functions of AlO are calculated. Comparisons of radiative lifetimes and line intensities of AlO are given. Temperature-dependent spectroscopy below 55, 000 cm −1 is presented. The electronic transitions from X 2 Σ + to A 2 Π, B 2 Σ +, C 2 Π and D 2 Σ + are important. Abstract: The spectrum of AlO is widely used in various applications including the explorations of interstellar space, studies of laser ablation, combustions of Al-containing fuels and so on. In this work, we reported the spectroscopy of the AlO radical at temperatures of 300 ∼ 15, 000 K for the wavenumber range of 1 ∼ 55, 000 cm −1 . Firstly, we extended our previous calculations of the potential energy curves (PECs) and transition dipole moments (TDMs) for AlO (Bai, Qin & Liu, MNRAS, 2022, 510:1649–1656) to higher B 2 Σ +, D 2 Σ +, 1′ 2 Π and 1′' 2 Π electronic states, with the consideration of Davidson correction, scalar relativistic correction and core-valence correlation. Partition functions, Einstein coefficients and radiative lifetimes of AlO were then obtained by solving the nuclear-motion Schrödinger equation. The partition functions reveal that the AlO molecules mainly exist in the X 2 Σ + state at temperatures of 10 ∼ 6270 K and in the A 2 Π state at temperatures of 6270 ∼ 15, 000 K in the thermodynamic equilibrium. Finally, line intensities and spectra for different electronic transitions of AlO were calculated. The results show that the X 2 Σ +  → C 2 Π and X 2 Σ +  → D 2 Σ + transitions dominate in the ultraviolet waveband. Comparisons of the TDMs, radiative lifetimes, line intensities and spectra with previous theoretical and experimental values indicate that our calculated data in the ultraviolet waveband are reliable and may be used for the radiation field calculation. Graphical abstract: Image, graphical abstract